Potentialities and limitations of computer-aided design and manufacturing technology in the non extraction treatment of Class I malocclusion - Moreira, Fernando Cesar [UNESP]; Vaz, Luis Geraldo [UNESP]; Guastaldi, Antonio Carlos [UNESP]; English, Jeryl D.; Jacob, Helder B. (Elsevier B.V., 2021)
Introduction: Computer-aided design and manufacturing (CAD-CAM) systems have assisted orthodontists to position brackets virtually. The purpose of this study was to evaluate if a CAD-CAM system could predict the orthodontic treatment outcome of patients with Angle Class I malocclusion with mild crowding or spacing and with no need for orthodontic extraction. Methods: Using the American Board of Orthodontics Cast-Radiograph Evaluation (ABO-CRE) and color map superimposition, the treated occlusion was compared with the virtual final occlusion of 24 young adults with Class I occlusion. Using eXceed software (eXceed, Witten, Germany), we created the final occlusion prediction for each patient (virtual set up group). A digital model of the final occlusion of each patient was created (treated occlusion group). ABO-CRE score was used to compare groups. In addition, a color map was created for all subjects to access the mean and range values between the virtual set up model and treated occlusion model of each patient. Random and systematic errors were calculated. In addition, chi-square and t test were used. Results: Comparisons between virtual set up occlusion and treated occlusion showed statistically significant differences in 3 out of 7 measurements: interproximal contact score was larger for treated than virtual occlusion (0.45 mm and 0.04 mm, respectively), and the treated occlusion showed larger values than the virtual occlusion for occlusal contacts (14.13 mm and 7.62 mm, respectively) and overjet (7.37 mm and 0.66 mm, respectively). Although the treated occlusion showed a larger score than the virtual occlusion (50.41 mm and 34.58 mm, respectively), there is no significant difference between both. Root angulation decreased (from 1.95 +/- 1.29 to 0.65 +/- 0.71) because of the treatment. Conclusion: ABO-CRE overall score presents no difference between groups. In addition, CAD-CAM setup occlusion closely predicts the final teeth alignment and leveling with interarch relationships showing less ABO-CRE score deduction.